Aptis as an Alternative English Language Proficiency Test: The USIM Experience - Noor Saazai Mat Saad; Fariza Puteh Behak; Ramiaida Darmi; Hazleena Baharun; Suzanah Selamat; Alfaiz Md Salleh (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia